AquaNet - PARAFAC component parameters from Bolmen AquaNet platform, 2022-07-07–2022-08-12 - Bolmen Research Station (Swedish University of Agricultural Sciences, 2024)
Data contains PARAFAC components to describe dissolved organic matter composition (DOM) from grab samples taken from the AquaNet mesocosms.
Bolmen Research Station (2024). AquaNet - PARAFAC component parameters from Bolmen AquaNet platform, 2022-07-07–2022-08-12 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/Vz0cFjZBbfdvmyaRtl5QlMgy
Keywords: SITES AquaNet; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap